2004
DOI: 10.1099/mic.0.26557-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the transcriptional activator XlnR from Aspergillus niger

Abstract: The transcriptional activator XlnR from Aspergillus niger is a zinc binuclear cluster transcription factor that belongs to the GAL4 superfamily. Several putative structural domains in XlnR were predicted using database and protein sequence analysis. Thus far, only the functionality of the N-terminal DNA-binding domain has been determined experimentally. Deletion mutants of the xlnR gene were constructed to localize the functional regions of the protein. The results showed that a putative C-terminal coiled-coil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 31 publications
3
91
0
Order By: Relevance
“…Regulation of hemicellulase gene expression has focused on induction by different inducers and transcriptional regulation mediated by XYR1/XlnR (25,31,34,38,51,63,64; also reviewed in references 52 and 61). In Aspergillus and H. jecorina, xlnR/xyr1 is also regulated by carbon catabolite repression (CCR) (16,44,53,56).…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of hemicellulase gene expression has focused on induction by different inducers and transcriptional regulation mediated by XYR1/XlnR (25,31,34,38,51,63,64; also reviewed in references 52 and 61). In Aspergillus and H. jecorina, xlnR/xyr1 is also regulated by carbon catabolite repression (CCR) (16,44,53,56).…”
Section: Discussionmentioning
confidence: 99%
“…For the samples of the debris pile, 6 ll of the supernatant was applied in the wells in duplicate. After 22 h of incubation at 25°C, the plates were photographed and the area of the blue halo surrounding each well [which is a quantitative measure for the amount of enzyme activity (Hasper et al, 2004;Schiøtt et al, 2008;Pedersen et al, 2009;] was measured using the software program ImageJ ver. 1.41 for Macintosh (Fig.…”
Section: Enzyme Assays and Screeningmentioning
confidence: 99%
“…For the A. niger XlnR protein, the possible participation of Ace1 in transcriptional regulation of hydrolase-encoding genes has not yet been shown, and an Ace2 homologue could not even be found in the genome. In addition, it was suggested that XlnR binds as a monomer since it was shown to bind to a nonpalindromic consensus in the promoter (14,48). In contrast to Xyr1, XlnR seems to act as an unspecific transactivator of a wide variety of genes encoding hydrolytic enzymes responding mainly to Dxylose induction, largely independent of other substrate-specific regulatory proteins.…”
Section: Vol 5 2006mentioning
confidence: 99%